Bringing Anti-Racism into Historical Explanation: The Victoria Chinese Students’ Strike of 1922-3 Revisited - Stanley, Timothy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2002)
AbstractAnti-racist theory draws attention to the socially constructed and contested nature of racial categories. This paper applies anti-racist theory to a case study of the 1922-3 Chinese students' strike in Victoria, British Columbia, and argues that school segregation was less about which schools students would attend and more about whether racialized Chinese people were part of, or could be part of, the imagined community of Canada as nation. Racialized discourse not only fixed “the Chinese” as outsiders to the imagined community, it also enacted colonialism by naturalizing the Anglo-European occupation of the territory of British Columbia. But there was also a significant group of Canadian-born Chinese in Victoria who had used provincially controlled schools to assimilate to dominant values and gain sufficient cultural capital to directly challenge racialized binaries. This group claimed “Canadianness” in their own right and staunchly resisted segregation. The intervention of Anglo-European anti-racists in the dispute further underlines the socially constructed and contested nature of racial categories. Finally, the more powerful fixing of Chinese as alien in Canada through the 1923 Chinese Immigration Act helps to explain the manner in which the students' strike came to close at the beginning of the 1923-4 school year.